A ratiometric fluorescent BODIPY-based probe for rapid and highly sensitive detection of cysteine in human plasma. Issue 23 (15th October 2018) - Wang, Nannan; Wang, Yue; Gao, Jinhua; Ji, Xin; He, Jinling; Zhang, Jian; Zhao, Weili
Abstract : The probe could respond to Cys/Hcy, exhibiting a ratiometric fluorescence response through intramolecular displacement with the amino group displacing the sulfur function to form amino-substituted BODIPY. Abstract : Biological thiols, especially low molecular weight thiols, including cysteine (Cys), homocysteine (Hcy) and glutathione (GSH), play a pivotal role in physiological and pathological systems. Thus, the detection of biothiols is highly important for early diagnosis of diseases and evaluation of disease progression. Herein, we developed a highly selective and sensitive ratiometric fluorescent 8-Cl BODIPY-based probe with high fluorescence quantum yields. The probe displayed a sensitive response to Cys and Hcy over other biothiols, which can be visualized colorimetrically and/or fluorescently. The probe was successfully applied to detect Cys in human plasma, demonstrating its great value for practical application in biological sample analysis.